Corneal transplantation: the fine line between donor shortage and tissue quality - Steger, Bernhard; Kaye, Stephen B; Romano, Vito (BMJ open ophthalmology, 2022)
The aim was to assess, whether there was an association between recorded donor characteristics such as endothelial cell density (ECD), age and sex, and endothelial graft failure and rejection. In response to this problem, England recently switched to an opt-out organ donation policy aiming to close the annual gap of approximately 1500 corneas, despite importing tissue from the USA and European Union (EU).10 However, the effect of this step remains to be quantified, being temporarily masked by a relative donor shortage due to Brexit and the aftermath of the COVID-19 pandemic, which significantly affected eye bank donor cornea procurement on a global scale.11 In addition, compared with other eye bank systems, such as in USA or Italy, the postmortem times such as death to retrieval, retrieval to processing and processing to issue may be skewed to being longer in the UK. The findings reported in this issue should push eye banks to try to keep improving postmortem times, and also to push basic science research into looking for novel, alternative ways to measure the true heath of endothelial cells as well as improving their health to increase graft survival.